INSIGHTS INTO QUALITATIVE VARIABLES ASSESSMENT IN MARKETING RESEARCH - Timiras, Laura Catalina (Studies and Scientific Researches. Economics Edition, 2014)
In this paper we present a number of issues to be taken into account in assessing the marketing qualitative variables. Thus, the opinions, the preferences, the attitudes, etc. of the consumers are qualitative variables whose measurement requires the use of different scales presented in the literature and, where appropriate, the researcher must develop scales adapted to the particularities of the study undertaken. Using a certain scale it is not random action. The literature presents both comparative methods and non-comparative scaling methods. Each of these categories generates certain types of information, and also they are complementary in the evaluation of various products, brands, organizations etc. Thus, if in a non-comparative scaling method can get information about how a product is evaluated (favorable or unfavorable, for example) by the respondents, comparative scaling method allows us to determine where that product is in a series of investigated competing products. Another aspect to be taken into account in the construction of the scales is the number of levels used. It is intended to obtain information with high degree of detail, but without the risk of increasing the rate of non-response due to inability of respondents to make assessments through scales with too many levels. Finally, the expression used to collect information from respondents is essential in obtaining accurate and comparable information, with the emphasis on avoiding ambiguity in drawing scales.